The Effectiveness of the Multimedia Phonological Awareness Program on The Reading Skill of students with borderline intellectual functioning in The First Grade - Samira Saeidi; Saeid Hassanzade; Sogand Ghasemzadeh (مطالعات روانشناسی تربیتی)
The purpose of the present study was to determine the effectiveness of the multimedia phonological awareness program on the reading skill of students with borderline intellectual functioning in the first grade. In this research, which was carried out as single-subject research and as baseline approach, the statistical population included students with borderline intellectual functioning of the first grade in Tehran. Among them, two female students with borderline intellectual functioning were selected by purposive sampling. One of these students had reading problems and the other had none. Then, the phonological awareness program was performed for them during 12 sessions of 45 minutes. Additionally, the subjects were evaluated in three stages with the Reading and Dyslexia test (NEMA). The results obtained from the visual analysis of the data and the effect size index indicated that the performance of both subjects in the subscales of the reading skill increased significantly in the intervention stage compared to the baseline stage. Therefore, it seems that the multimedia phonological awareness program is effective in increasing the reading skill of students with borderline intellectual functioning in the first grade.